Reward management in a small IT business - Novotný, Lukáš; Dvořáková, Zuzana, 1960-; Cetkovský, Pavel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The topic of this thesis is reward management and its application in a small-sized IT enterprise. Its goals are to properly document and describe current reward system in the company, evaluate the system and recommend improvements for the system. The first two goals are reached via thorough research of the company through semi-structured interviews, employee satisfaction survey, participant observation and document examination and the last one by applying principles from the current literature and education to the results of the two previous goals. The findings are that the reward system, despite growing organically instead of designed, is relatively effective in some areas, but needs improvement in other areas. The main improvement areas are motivation by contingent pay, communication management and performance management. Relatively well working rewards are especially non-financial reward connected to the work environment and work itself.
Vedoucí práce: Zuzana Dvořáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses